UAV and photogrammetry for 3D digitalization - Tan, Joanne Xin Yi (Nanyang Technological University, 2020)
Building and Information Modelling (BIM) is an indispensable tool used by architecture, engineering, and construction industries. The shift from two-dimensional floorplans to three-dimensional BIM models allows for better visualization of building projects. In addition, BIM models can be used for areas such as conflict detection in the planning phase, and for facilities management for existing buildings. However, as BIM is a relatively new technology employed in the architecture and construction industry, existing buildings may not have complete and up-to-date BIM models. There is an interest in surveying techniques for creating as-built BIM models for existing buildings. Common surveying techniques include imaged-based techniques such as photogrammetry and videogrammetry, as well as range-based techniques such as laser scanning. Imaged-based techniques are an attractive option for surveying due to its low equipment cost and portability. Camera mounted on platforms such as Unmanned Aerial Vehicles (UAV) offers added advantage such as capturing data from inaccessible areas and reducing data collection time. This project investigated the possible use of a commercial UAV product, DJI Mavic Air, for photogrammetry. The photogrammetry software used in this project is Autodesk Recap Pro. Research was conducted and the optimal camera settings and parameters for obtaining quality point cloud data of Mechanical, Plumbing, and Electrical (MEP) elements of a Housing and Development Board (HDB) flat was determined. A suggested workflow for photogrammetry of MEP elements is presented in this project.